Evidence for the Role of Active Site Residues in the Hairpin Ribozyme from Molecular Simulations along the Reaction Path - Heldenbrand, Hugh (American Chemical Society, 2014)
[Image: see text] The hairpin ribozyme accelerates a phosphoryl transfer reaction without catalytic participation of divalent metal ions. Residues A38 and G8 have been implicated as playing roles in general acid and base catalysis, respectively. Here we explore the structure and dynamics of key active site residues using more than 1 μs of molecular dynamics simulations of the hairpin ribozyme at different stages along the catalytic pathway. Analysis of results indicates hydrogen bond interactions between the nucleophile and proR nonbridging oxygen are correlated with active inline attack conformations. Further, the simulation results suggest a possible alternative role for G8 to promote inline fitness and facilitate activation of the nucleophile by hydrogen bonding, although this does not necessarily exclude an additional role as a general base. Finally, we suggest that substitution of G8 with N7- or N3-deazaguanosine which have elevated pK(a) values, both with and without thio modifications at the 5′ leaving group position, would provide valuable insight into the specific role of G8 in catalysis.